Perlindungan Hukum Terhadap Benda Cagar Budaya Studi Kasus Di Pengadilan Negeri Surakarta - Wibowo, Danang Ari, Prof.Dr.Khudzaifah Dimyati, Dr.Natangsa Surbakti (2016)
In the State of Indonesia there are so many objects of historic and archaeological heritage. Historic relics and archaeological such a priceless wealth of this nation, which is very essential and even mandatory to be treated, well run and very necessary to be preserved. The objects of the historical and archaeological heritage which is in accordance with the qualifications prescribed by law commonly referred to as objects of cultural heritage. The existence of objects of cultural heritage is still prone to damage, loss and perhaps to extinction, whether caused by natural factors and deeds of the man himself.Type This research uses qualitative research and the nature of the study is a descriptive study that is by the way said or interpret the data contained in Surakarta District Court.Results from this study is that the legal protection of the objects of cultural heritage in Indonesia is in the presence of Act No. 5 of 1992 on Objects of that has now been enhanced by Act No. 11 of 2010 on the cultural heritage. Law enforcement for violators of the law of cultural heritage is a form of imprisonment in accordance with clauses that.